WeatherLAN - A Local Area Network for Monitoring and Control - Wik, Niklas (My University, 2009)
Monitoring of nature behaviours is a crucial part in many applications. The need for monitoring is in fact unavoidable in systems where independent operation of a system is needed. On locations where no cabled infrastructure is available it is necessary to use wireless link to interconnect the location with the Internet. GPRS is a cheap solution for transferring data over such areas where cables are not available by using operator public cellular network. In this thesis a wireless sensor network is integrated with a GPRS module to support multiple measurement points and GPRS link as backbone connection to remote location. Security issues related to embedded systems and the use of public networks is investigated and one possible solution presented. Vaisala WXT520 weather transmitter is added to the system to measure the weather at the network location which would be needed to remotely support the distributed energy production by wind turbine generator, solar panels and backup diesel generator. The system prevent to be one solution that would enable remote control of the local energy production.
Keywords: WSN; IEEE 802.15.4; GPRS; fi=Tietoliikennetekniikka|en=Telecommunications Engineering|; fi=Tietotekniikan koulutusohjelma (DI)|